Implications of Russia’s war in Ukraine for Belarus and its society: what is exactly written in the EU documents? - Kascian, Kiryl (Public Governance, Administration and Finances Law Review, 2022)
This article provides an assessment of the relevant EU documents pertinent to the restrictive measures against Lukashenka’s regime after the 2020 fraudulent presidential elections in Belarus and since the beginning of 2022 Russia’s aggression against Ukraine. The text identifies relevant concepts and provides their contextual analysis vis-à-vis their linkage with Belarus in general, its society and Lukashenka’s regime. The article reveals that Belarus did not become a priority of the EU and its pre-war critical engagement policy failed to contribute to the development of a unified EU-wide vocabulary addressing the Belarusian case. With the start of the war, it was internationalised and placed within a binarity “victim of aggression – (co-)aggressor” with little evidence of an unequivocal shift towards a primary focus on the contextual interpretation of the domestic developments in Belarus.ts in Belarus.